Inside vanguard leadership secrets from the company that continues to rewrite the rules of the investing business - Ellis, Charles D. (McGraw-Hill Education, 2023)
"This rare intimate look at Jack Bogle and his world-changing investment organization provides invaluable lessons for investors, for business leaders, and for historians of finance"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Bogle, John C; Vanguard Group of Investment Companies; Chief executive officers -- Biography -- United States; Mutual funds -- United States; Investments -- United States; Corporate governance -- United States; Chefs de direction; États-Unis; Biographies; Investissements; États-Unis; Gouvernement d'entreprise; États-Unis; Chief executive officers; Corporate governance; Investments; Mutual funds; United States; Biographies